Biomechanical Comparison of Flexor Digitorum Profundus Avulsion Repair - Putnam, Jill G.; Adamany, Damon (Journal of Wrist Surgery, 2019)
Purpose Multiple repair techniques have been investigated for flexor digitorum profundus (FDP) tendon avulsions. The purpose of this study is to compare the biomechanical characteristics of a new fully threaded titanium suture anchor with previously examined fixation techniques.Methods Repair of FDP tendon avulsions was performed in 18 fresh-frozen cadavers using one of three implants: Nano Corkscrew FT 1.7 mm suture anchor (Group 1; Arthrex, Inc., Naples, FL; n = 6), Mitek Micro 1.3 mm suture anchor (Group 2; Mitek Surgical Products, Westwood, MA; n = 6), or pullout suture button fixation (Group 3; n = 6). Constructs were preloaded before testing load to failure. For each trial, elongation at 20 N and maximum load, mean load to failure, stiffness, and failure mechanism were recorded.Results Load to failure occurred in all trials. Mean load to failure was significantly greater for Group 1 (61.6 ± 18.9 N) compared to Group 2 (42.5 ± 4.2 N; p < 0.05) and Group 3 (41.6 N ± 8.0 N; p < 0.05). Stiffness was significantly greater in Groups 1 and 2 compared to Group 3 (6.9 ± 2.2 N/mm vs. 6.1 ± 0.8 N/mm vs. 3.1 N/mm ± 0.5 N/mm, respectively, p < 0.01). Mechanism of failure differed between the groups: Group 1 broke at the anchor in two trials and tore through the tendon in three trials, Group 2's suture universally broke at the anchor, and Group 3's trials mainly failed at the button.Conclusions The Nano Corkscrew anchor (Group 1) has a significantly higher load to failure when compared with the other techniques. The higher load to failure of the corkscrew anchor provides a secure method for flexor tendon repair in zone I.Clinical Relevance A fully threaded titanium suture anchor used for FDP tendon avulsion injuries is likely to withstand early active range of motion protocols.
Keywords: flexor; tendon; avulsion; repair; biomechanical